Comparison of distinctive models for calculating an interlobar emphysema heterogeneity index in patients prior to endoscopic lung volume reduction - Theilig, Dorothea (Int J Chron Obstruct Pulmon Dis, 2017)
BACKGROUND: The degree of interlobar emphysema heterogeneity is thought to play an important role in the outcome of endoscopic lung volume reduction (ELVR) therapy of patients with advanced COPD. There are multiple ways one could possibly define interlobar emphysema heterogeneity, and there is no standardized definition. PURPOSE: The aim of this study was to derive a formula for calculating an interlobar emphysema heterogeneity index (HI) when evaluating a patient for ELVR. Furthermore, an attempt was made to identify a threshold for relevant interlobar emphysema heterogeneity with regard to ELVR. PATIENTS AND METHODS: We retrospectively analyzed 50 patients who had undergone technically successful ELVR with placement of one-way valves at our institution and had received lung function tests and computed tomography scans before and after treatment. Predictive accuracy of the different methods for HI calculation was assessed with receiver-operating characteristic curve analysis, assuming a minimum difference in forced expiratory volume in 1 second of 100 mL to indicate a clinically important change. RESULTS: The HI defined as emphysema score of the targeted lobe (TL) minus emphysema score of the ipsilateral nontargeted lobe disregarding the middle lobe yielded the best predicative accuracy (AUC =0.73, P=0.008). The HI defined as emphysema score of the TL minus emphysema score of the lung without the TL showed a similarly good predictive accuracy (AUC =0.72, P=0.009). Subgroup analysis suggests that the impact of interlobar emphysema heterogeneity is of greater importance in patients with upper lobe predominant emphysema than in patients with lower lobe predominant emphysema. CONCLUSION: This study reveals the most appropriate ways of calculating an interlobar emphysema heterogeneity with regard to ELVR.